2013
DOI: 10.11118/actaun201260080019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alginure® (seaweed extract), Myco-Sin®VIN (sulfuric clay) and Polyversum® (Pythium oligandrum Drechs.) on yield and disease control in organic strawberries

Abstract: BOČEK, S., SALAŠ, P., SASKOVÁ, H., MOKRIČKOVÁ, J.: Eff ect of Alginure® (seaweed extract), MycoSin®VIN (sulfuric clay) and Polyversum® (Pythium oligandrum Drechs.) on yield and disease control in organic strawberries. Acta univ. agric. et silvic. Mendel. Brun., 2012, LX, No. 8, pp. 19-28 In 2011 and 2012 three commercial products Alginure® (seaweed extract), Myco-Sin® VIN (sulfuric acid clay with yeast and plant extracts) and Polyversum® (spores of Pythium oligandrum) were tested in fi eld experiment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…This concurs with previous research that showed seaweed extracts from A. nodosum could increase strawberry fruit yields by up to 30% (Spenelli et al 2010 ; Alam et al 2013 ; El-Miniawy et al 2014 ). In contrast, Boček et al ( 2012 ) showed that a mixture of seaweed extract and amino acids did not increase strawberry fruit yields in an organic system in Europe. The seaweed extract in the trial by Boček et al ( 2012 ), however, was only applied as a foliar treatment and was applied less frequently (five times through the cropping cycle) than in the current trial.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This concurs with previous research that showed seaweed extracts from A. nodosum could increase strawberry fruit yields by up to 30% (Spenelli et al 2010 ; Alam et al 2013 ; El-Miniawy et al 2014 ). In contrast, Boček et al ( 2012 ) showed that a mixture of seaweed extract and amino acids did not increase strawberry fruit yields in an organic system in Europe. The seaweed extract in the trial by Boček et al ( 2012 ), however, was only applied as a foliar treatment and was applied less frequently (five times through the cropping cycle) than in the current trial.…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, Boček et al ( 2012 ) showed that a mixture of seaweed extract and amino acids did not increase strawberry fruit yields in an organic system in Europe. The seaweed extract in the trial by Boček et al ( 2012 ), however, was only applied as a foliar treatment and was applied less frequently (five times through the cropping cycle) than in the current trial. The increase in strawberry fruit yield by the seaweed extract in the current trial also increased revenue from fruit by 8% or AUS$0.30 per plant, which is a significant return for strawberry growers compared with the cost of the treatment.…”
Section: Discussionmentioning
confidence: 90%
“…The obtained results from all variants were similar. Boček et al (2012) used commercial products Alginure (Tilco Biochemie GmBH, Germany), Myco-Sin® VIN (Dr. Schaette AG, Germany) and Polyversum ® (Biopreparaty Ltd., Czech Republic) and they observed lower occurrence of grey mould in majority variants in comparison with control. Using of apple tree wood chips for support of development microbial community in soil and plant debris, which could decrease level of occurrence of grey mould does not give positive results at least similar as give above-mentioned commercial products.…”
Section: Discussionmentioning
confidence: 99%
“…A number of merits can be mentioned in favour of biological insecticides, including neem and pyrethrum, in this respect: 1) the proved efficacy of the neem products under field conditions; 2) its environmentally friendly characteristics coupled with its harmless or minimal side-effects on the main natural enemies; 3) the great enthusiasm of the farmers for available inexpensive pesticide and their willingness to use it in their crop fields (El Shafie, 2001). 10 (Cholakov & Boteva, 2012) and those of Polyversum present mainly the fungicidal effect of the product (Gewehr, 2011;Boček et al, 2012). The most pronounced effect among organic products applied alone had foliar fertilizer Biofa based on algae extract that led to an increase by 9.8% on average over the control.…”
Section: Discussionmentioning
confidence: 99%